Optical and Photoluminescence Properties of Eu3+ ion doped Gadolinium Silica-phosphate Glasses - Elyzabeth Simanullang; Winsyahputra Ritonga; Juniastel Rajagukguk; Donna Helen Rajagukguk; Chayani Sarumaha; Jakrapong Kaewkhao (Program Studi Fisika Universitas Negeri Jakarta, 2026)
Eu3+-doped gadolinium silica-phosphate glasses with compositions of 57P2O5–15QS–15CaO–5BaO–5Gd2O5–3Eu2O3 (PCBGO) and 57P2O5–15QS–15CaO–5BaO–5GdF3–3Eu2O3 (PCBGF) were successfully synthesized using the melt-quenching technique employing natural quartz sand from Huta Ginjang, North Sumatra, Indonesia, as a silica source. The structural, optical, and photoluminescence properties of the prepared glasses were systematically investigated through X-ray diffraction (XRD), Fourier Transform Infrared (FTIR), UV-Vis-NIR absorption spectroscopy, photoluminescence spectroscopy, Judd-Ofelt (J-O) analysis, lifetime measurements and CIE chromaticity analysis. XRD results confirmed the amorphous characteristics of both glasses, while FTIR spectra revealed the formation of silica-phosphate structural networks. The incorporation of GdF3 significantly improved glass transparency and reduced hydroxyl-related defects compared with Gd2O3 containing glass. Absorption spectra exhibited characteristic Eu3+ transitions at 392, 464, 531, 2085, and 2210 nm. Judd-Ofelt analysis demonstrated that PCBGF glass possessed a higher Ω2 parameter, indicating increased local asymmetry and stronger covalent interaction around Eu3+ ions. Excitation and emission spectra revealed intense red luminescence dominated by the hypersensitive 5D0 ® 7F2 transition centered at 613 nm. The PCBGF glass exhibited superior photoluminescence intensity, larger stimulated emission cross-section, and enhanced radiative efficiency due to the lower phonon energy of the fluoride-containing host matrix. Lifetime analysis showed experimental decay times of 1.823 and 1.029 ms for PCBGO and PCBGF, respectively, indicating enhanced radiative transition probability in PCBGF glass. The chromaticity coordinates for both glasses were determined to be (0.571, 0.302), located within the red region of the CIE 1931 diagram. These findings demonstrate that fluoride incorporation effectively enhances the optical and luminescence properties of Eu3+-doped silica-phosphate glasses, making PCBGF a promising material for red phosphors, optical amplifiers, solid-state lasers, and advanced photonic applications.